2022
DOI: 10.1080/14756366.2021.2018682
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and bioactivities evaluation of oleanolic acid oxime ester derivatives as α-glucosidase and α-amylase inhibitors

Abstract: Different oleanolic acid (OA) oxime ester derivatives ( 3a - 3t ) were designed and synthesised to develop inhibitors against α -glucosidase and α -amylase. All the synthesised OA derivatives were evaluated against α -glucosidase and α -amylase in vitro. Among them, compound 3a showed the highest α -glucosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…For instance, cyanidin (one of TOTUM-63 anthocyanins), apigenin, luteolin-7-O-glucoside, and oleanolic acid exert strong inhibitory effects on α-glucosidase [ 45 , 46 , 47 , 48 ]. Oleanolic acid showed the strongest effect with 162 times higher inhibitory activities on α-glucosidase compared with acarbose (IC 50 = 4.09 µM for oleanolic acid and IC 50 = 665.56 µM for acarbose) [ 49 ]. Moreover, other studies have demonstrated major or minor inhibitory effects on α-glucosidase for several other compounds identified in TOTUM-63: apigenin-7-O-glucuronide, dicaffeoylquinic acids (including cynarin), eriodictyol, marein, flavanomarein, and apigenin-6,8-C-diglucoside (vicenin 2) [ 50 , 51 , 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, cyanidin (one of TOTUM-63 anthocyanins), apigenin, luteolin-7-O-glucoside, and oleanolic acid exert strong inhibitory effects on α-glucosidase [ 45 , 46 , 47 , 48 ]. Oleanolic acid showed the strongest effect with 162 times higher inhibitory activities on α-glucosidase compared with acarbose (IC 50 = 4.09 µM for oleanolic acid and IC 50 = 665.56 µM for acarbose) [ 49 ]. Moreover, other studies have demonstrated major or minor inhibitory effects on α-glucosidase for several other compounds identified in TOTUM-63: apigenin-7-O-glucuronide, dicaffeoylquinic acids (including cynarin), eriodictyol, marein, flavanomarein, and apigenin-6,8-C-diglucoside (vicenin 2) [ 50 , 51 , 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The α-glucosidase inhibition of synthetic compounds was performed as previously reported methods with minor modification ( Deng et al, 2022 ) which is as follows: briefly, 130 μl of phosphate buffer (10 mM, pH 6.8), 10 μl of α-glucosidase (1 U/ml), and 10 μl of test compound solution were added into the wells of a 96-well plate, followed by incubation for 10 min at 37°C. Then, 50 μl of p -NPG (1 mM) was added, and the plate was further incubated for 30 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Characteristics of mellowness, matureness, and smoothness of CTLs were improved obviously. The addition of α-amylase could promote the production of polysaccharide effectively, thus improving the sweetness of CTLs (Deng et al, 2022). However, thickened protein odor with the addition of three enzymes could not be ignored, which may be caused by the excessive addition amount of enzyme.…”
Section: Flavourzymementioning
confidence: 99%